The Post-Discharge Network Coordination Programme: A Randomized Controlled Trial to Evaluate the Efficacy of an Intervention Aimed at Reducing Rehospitalizations and Improving Mental Health - Hengartner, Michael P.; Passalacqua, Silvia; Heim, Gisela; Andreae, Andreas; Rössler, Wulf; von Wyl, Agnes (Frontiers in Psychiatry, 2016)
Purpose: To evaluate the efficacy of a post-discharge intervention for psychiatric inpatients aimed at preventing hospital readmissions and at improving patients’ mental health and psychosocial functioning. Methods: RCT using parallel group block randomisation including 151 patients with ≤3 hospitalisations within the last three years, a GAF score ≤60, and aged 18–64 years, assessed at two psychiatric hospitals from the canton of Zurich, Switzerland, between September 2011 and February 2014. Primary outcomes were rate and duration of rehospitalisation; secondary outcomes were mental health and functioning. Outcome measures were assessed before discharge from the index hospitalisation (t0), 3 months after discharge when the intervention terminated (t1), and 12 months after discharge (t2). Participants received either a brief case management post-discharge intervention or treatment as usual. Results: In the short-term (i.e., t0-t1) no significant effect emerged in any outcome. In the long-term (i.e., t0-t2) the two groups did not differ significantly with respect to the rate and duration of rehospitalisation. Also, the intervention did not reduce psychiatric symptoms, did not improve social support and did not improve quality of life. However, it did slightly increase assessor-rated general (d=0.30) and social functioning (d=0.42), although self-reports revealed a deteriorative effect on symptom remission (d=-0.44). Conclusions: This psychosocial post-discharge intervention showed no efficacy in the primary outcome of rehospitalisation. With respect to secondary outcomes, in the long-term it might lead to slightly increased social functioning but revealed no significant effect on psychopathology, social support and quality of life. In contrast, with respect to self-reported symptom remission, it was revealed to have a negative effect. In this high-resource catchment area with comprehensive community psychiatric and social services the intervention thus cannot be recommended for implementation in routine care. Funding: This study was supported by a private foundation. Trial registration: ISRCTN58280620